Predictors of relapse of acute malnutrition following exit from community-based management program in Amhara region, Northwest Ethiopia: An unmatched case-control study. - Dereje Birhanu Abitew; Alemayehu Worku Yalew; Afework Mulugeta Bezabih; Alessandra N Bazzano (PLoS ONE, 2020)
Background Community-based management of acute malnutrition (CMAM) is an effective program to manage children with acute malnutrition, including both severe and moderate acute malnutrition. However, little is known about continued child nutritional status after discharge from community based management of acute malnutrition programs in Ethiopia. Objective The study aimed to identify factors associated with relapse of acute malnutrition among children 6-59 months after been discharged recovered from community based management program in South Gondar Zone, Northwest Ethiopia. Methods A case-control study was conducted in three districts of South Gondar Zone by tracing children age 6-59 months who were reported as recovered from the community based management program. Sample size calculated for the first objective of assessing prevalence of severe acute malnutrition among children following discharge as recovery using Epi- Info version 7.1.3.3 StatCalc taking 95% CL, 17.8% post discharge relapse (Ashraf H, et al. (2012), 3% margin of error, design effect of 2 and adding 5% non-response rate was the largest sample size and used to this study. Children with Mid Upper Arm Circumference (MUAC) <12.5cm constituted cases and children with > = 12.5cm served as controls. Data were collected from 10 November 2017 to 30 January 2018 using a survey questionnaire and families were asked to bring children to a health facility for anthropometric measurements, following which data were entered and analyzed. Bivariate and multivariable logistic regression models were utilized to measure association between the risk factors and acute malnutrition. Results Overall, 1,273 participants were interviewed. The mean age in months of children was 23.1 (±9.1 SD) for cases and 23.1 (±8.9 SD) for controls. About 40% of the cases and 50% of the controls were female children. The factors associated with acute malnutrition were: male children (AOR = 1.84, 95% CI: 1.42-2.39), living in a food insecure household (AOR = 1.67, 95% CI:1.15-2.44), non-receipt of Vitamin A supplement (AOR = 1.76, 95% CI: 1.28-2.41), prelacteal feeding (AOR = 2.81 (95%CI, 1.57-5.05), distance to water source more than 15 walk (AOR = 1.88, 95% CI:1.32-2.71), less frequent self-reported hand washing (AOR = 1.35, 95% CI:1.05-1.75), mother not having consumed extra food during this pregnancy/lactation (AOR = 1.36, 95% CI: 1.03-1.78), and respondent age above 30 years (AOR = 1.43, 95% CI:1.10-1.87). Conclusion The key factors contributing to relapse of acute malnutrition were related to childcare and feeding practices. Social and behavior change communication strategies targeting families at risk of undernutrition, along with improved food security and integrated programming are recommended to prevent relapse of acute malnutrition.